Improvement of the NPS and FCR indicator in a company in the call center sector - García Gallo, Alonso Fernandino (2024)
The objective of this research is to show a work plan for the improvement of the NPS (net promoter score) and FCR (first call resolution) indicators in a company of the Call Center sector, using continuous improvement tools for the optimization of the process. The research begins with the identification of the problem detailing historical data of the NPS and FCR indicators, contextualization and understanding of the problem, justification of the problem showing a total loss of S/666 750 soles in the first half of 2022 for not meeting the objective, analysis of the causes, implementation of improvements in the processes of greater impact and that is applicable transversely to the entire organization globally, results of the improvements implemented with data obtained in the second half of 2022 of S/ 540 000 and projection of benefits for the year 2023 of S/ 794 000.